STUDENTS' PERCEPTIONS AND ATTITUDES: IMPLEMENTATION OF VIRTUAL LABORATORY PHYSICS APPLICATIONS (PVL) DURING THE COVID-19 PANDEMIC - Nindha Ayu Berlianti; Nur Hayati; Lina Arifah Fitriyah (JURNAL PENA SAINS, 2021)
The coronavirus outbreak from 2019 had a significant impact on all sectors in Indonesia, especially the education sector, which requires learning from home. It provides a change in students' learning style to make educators change online-based learning using various platforms, one of which is the Physics Virtual Lab (PVL). This application is in a simulation designed explicitly physics practicum, accessed using a mobile phone. This study aims to determine how effective the use of PVL in fulfilling practicum activities is in terms of perceptions and competencies of students' attitudes. The research method is descriptive research to obtain an overview of PVL applications in physics practicum using domestic used materials. The subjects in this study were students of the first-semester science education study program who took the Basic Physics course—collecting data using perception questionnaires and attitude assessment sheets. The average student perception score is 4.22. Then, the students' attitude competence results obtained an average score of 80.88 integrity; independence 74.89; confidence 75.17 and responsibility 84.89. It shows that the implementation of PVL builds students' integrity and responsibility.